The ARCTA Prototype: An english writing tool and grammar checker for French-speakers - Tschumi, Corinne; Bodmer, Franck; Cornu, Etienne; Grosjean, François; Grosjean, Lyslane; Kübler, Natalie; Tschichold, Cornelia (Travaux neuchâtelois de linguistique, 1994)
[Se référer au PDF pour le résumé].